Project appraisal document on a proposed credit in the amount of SDR 83.9 million (US (The World Bank, 2006)
Contents of the book includes: Strategic context and rationale; project description; Implementation; Appraisal summary; Economic and fianancial analyses; Technical; Environment; Safeguard policies